STRATEGI HEDGING PADA PENGELOLAAN HUTANG LUAR-NEGERI PEMERINTAH INDONESIA TERHADAP RESIKO FLUKTUASI NILAI TUKAR US DOLLAR - Mrs Miksalmina (Quantitative Economics Journal, 2015)
During this time, the position of External Debt (ED) government has always had the exposure risk from a fluctuations in foreign currency exchange rates to USDollar. Usually, the ED values to swell because of the risk of weakening of the Rupiah against the USDollar. This study aims to look at the effectiveness of hedging strategies on the management of the government's foreign debt of Indonesia to the risk of exchange rate fluctuations of US dollar, by making a simulation of hedging forward contracts. A hedging strategy with a new forward contract will be executed if the rate exceeds Rp 10,000 per USDollar as psychological level. In this simulation, the Government applied a hedging strategy by purchasing forward contracts. This purchasing strategy will generate profits only when the values of forward contracts of USD / IDR weakened at the maturity date later. But if the opposite happens, then potential losses will occur. To minimize the potential loss, wee need this necessary analysis of historical and technical movement of the rupiah against the USDollar, followed by mechanisms of active trading. Active trading allows the government took the position prior purchases or sales in forward contracts advance, depending on the signal and market trends that occurred at that time. By hedging forward contracts, the resulting changes in the value of external debt on the simulation type 2 is much lower. In other words, it shows that the real strengthening of the rupiah with hedging strategies can ease the burden of official external debt, so it can be quite effective to reduce the external debt burden of the government when the time payment or maturity date is come.